1988
DOI: 10.1111/j.1600-0765.1988.tb01359.x
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase activity and protein content of sulcular fluid after scaling and occlusal adjustment of teeth with deep periodontal pockets

Abstract: Three teeth from each of 14 adult patients with advanced periodontitis were included in this study. The Test Tooth was an incisor or canine with increased mobility associated with an occlusal interference and a ≥ 5 mm deep pathologic pocket. The Infected Control Tooth was a non‐mobile incisor or canine with a ≥ 5 mm pocket. A non‐mobile incisor or canine with pockets ≤3 mm served as the Healthy Control Tooth. At least 7 d prior to Day 0 the patients were taught an effective oral hygiene regimen and received a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
6

Year Published

1990
1990
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 31 publications
2
21
0
6
Order By: Relevance
“…Conversely, the total amount of matrix metalloproteinases in the periodontium as well as the ratio of active to latent enzyme are decreased following periodontal therapy (Hakkarainen et al, 1988;McCulloch, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the total amount of matrix metalloproteinases in the periodontium as well as the ratio of active to latent enzyme are decreased following periodontal therapy (Hakkarainen et al, 1988;McCulloch, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Collagenase activity in gingival crevicular fiuid has been shown to decrease in response to periodontal treatment also in previous studies (13)(14)(15) and it has been suggested to correlate primarily with pocket depth (14). In these studies, however, only total collagenase activity was monitored.…”
Section: Discussionmentioning
confidence: 91%
“…Interstitial collagenases are secreted from the cells into the extracellular space in a latent form which is subsequently activated by the disease process (12). Increased collagenase activities have been reported in inflamed human gingiva and gingival crevicular fluid in respect to healthy tissues and this increased collagenase activity has been shown to decrease in response to treatment procedures (13)(14)(15)(16). Only recently was it shown that the predominant collagenolytic activity in gingival crevicular fluid of patients with adult periodontitis is MMP-8 (10,(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Occlusal adjustment is defined as “reshaping the occluding surfaces of teeth by grinding to create harmonious contact relationships between the maxillary and mandibular teeth.” The evidence linking occlusal adjustment to improvement in periodontal parameters is limited. In an earlier study, the flow rate and quality of gingival crevicular flow (GCF) after removal of occlusal interferences was examined in patients with advanced periodontitis . It was found that occlusal adjustment reduced the protein content and collagenase activity without affecting the quantity of GCF.…”
Section: Narrative Reviewmentioning
confidence: 99%